Udział Anglii w wojnie Habsburgów z Francją w latach 1557-1558 - Makówka, Magdalena (Saeculum Christianum. Pismo Historyczne, 2020)
The purpose of this article is to present English participation in the war between France and the Habsburg Monarchy during the reign of Mary I. The queen's husband was Filip Habsburg, son of Emperor Charles V, and it was he who persuaded the English Secret Council to participate in the conflict. This war proved to have catastrophic consequences for England, due to the loss of Calais by the country of Mary I.